Assessment of Substrate Physical Properties in Bark- and Peat-based Stratified Substrate Systems - Jeb S. Fields; Kristopher S. Criscione; James S. Owen Jr (HortScience)
Soilless substrate stratification is increasing in popularity in the greenhouse and nursery industry globally. The concept of stratifying substrates entails stacking two substrates with different physiochemical properties to augment vertical moisture balances and redistribution for quicker establishment, greater root growth, and quicker time to market. Stratified substrate research to date has estimated or assumed that the static physical properties of a stratified system as the mean of the individual strata components. No research to date has verified or rejected this assumption using a stratified column. The research herein measured the static physical properties of 1) peatlite (85% peat: 15% perlite), 2) unprocessed <12.7 mm aged bark, 3) fine bark particles (≤6.3 mm), and 4) coarse bark particles (≥6.3 mm). Moreover, these physical properties were measured via 1) using the standard promoter analysis (7.6 cm core), 2) extending the core height by stacking two standard porometer cores (15.2 cm height) of the same strata component atop each other (to identify how water storage and air-filled porosity changes), and 3) stratifying either peatlite over unprocessed bark or fine bark over coarse bark. The results showed that extending the height of the porometer increased drainage and decreased water storage across conventional and stratified systems alike, illustrating the benefit of using cores equivalent to container height when making cultural decisions to manage water efficiently. When stratifying substrates, the system as a whole stores less water and has more air-filled porosity than nonstratified composite profiles (100% peatlite; 100% unprocessed bark) due to gravitational forces draining the higher portion of the container. Assumptions regarding the static physical properties of a stratified system can be made with the standard or extended porometer core for coarse-textured bark substrates used generally in the nursery industry with reasonable accuracy (<5% difference), meaning that nursery growers interested in stratifying their substrates can assess their stratified static physical properties using standard measurements. However, assumptions cannot accurately be assessed for finer peat-based stratified profiles used in greenhouse production and may require further refinement for estimations. The broader implications of this research highlight the storage capacities of a stratified substrate system, which may influence growers’ decisions in application and irrigation management.